Gut dysbiosis, inflammation and type 2 diabetes in mice using synthetic gut microbiota from diabetic humans - Liaqat,I. (2023)
Abstract The study was aimed to assess impact of high fat diet (HFD) and synthetic human gut microbiota (GM) combined with HFD and chow diet (CD) in inducing type-2 diabetes (T2D) using mice model. To our knowledge, this is the first study using selected human GM transplantation via culture based method coupled dietary modulation in mice for in vivo establishment of inflammation leading to T2D and gut dysbiosis. Twenty bacteria (T2D1-T2D20) from stool samples of confirmed T2D subjects were found to be morphologically different and subjected to purification on different media both aerobically and anerobically, which revealed seven bacteria more common among 20 isolates on the basis of biochemical characterization. On the basis of 16S rRNA gene sequencing, these seven isolates were identified as Bacteroides stercoris (MT152636), Lactobacillus acidophilus (MT152637), Lactobacillus salivarius (MT152638), Ruminococcus bromii (MT152639), Klebsiella aerogenes (MT152640), Bacteroides fragilis (MT152909), Clostridium botulinum (MT152910). The seven isolates were subsequently used as synthetic gut microbiome (GM) for their role in inducing T2D in mice. Inbred strains of albino mice were divided into four groups and were fed with CD, HFD, GM+HFD and GM+CD. Mice receiving HFD and GM+modified diet (CD/HFD) showed highly significant (P<0.05) increase in weight and blood glucose concentration as well as elevated level of inflammatory cytokines (TNF-α, IL-6, and MCP-1) compared to mice receiving CD only. The 16S rRNA gene sequencing of 11 fecal bacteria obtained from three randomly selected animals from each group revealed gut dysbiosis in animals receiving GM. Bacterial strains including Bacteroides gallinarum (MT152630), Ruminococcus bromii (MT152631), Lactobacillus acidophilus (MT152632), Parabacteroides gordonii (MT152633), Prevotella copri (MT152634) and Lactobacillus gasseri (MT152635) were isolated from mice treated with GM+modified diet (HFD/CD) compared to strains Akkermansia muciniphila (MT152625), Bacteriodes sp. (MT152626), Bacteroides faecis (MT152627), Bacteroides vulgatus (MT152628), Lactobacillus plantarum (MT152629) which were isolated from mice receiving CD/HFD. In conclusion, these findings suggest that constitution of GM and diet plays significant role in inflammation leading to onset or/and possibly progression of T2D. .